Cerebral Infarctions After Transcatheter Aortic Valve Replacement of Horizontal Aorta Versus Non-Horizontal Aorta - Hanyi Dai; Dao Zhou; Wenjing Sheng; Rongrong Zheng; Jun Chen; Abuduwufuer Yidilisi; Xianbao Liu; Lihan Wang (Journal of Clinical Medicine, 2026)
Background/Objectives: Horizontal aorta, characterized by a high aortic angle, represents a challenging anatomical feature during transcatheter aortic valve replacement (TAVR), but its association with cerebral ischemic injury remains unclear. This study investigated the association between horizontal aorta and diffusion-weighted magnetic resonance imaging (DW-MRI)-detected cerebral infarctions after TAVR. Methods: We retrospectively enrolled 411 consecutive patients with severe aortic stenosis undergoing transfemoral self-expanding TAVR between March 2017 and May 2022. Aortic angle was defined as the angle between the aortic annular plane and the horizontal plane on preprocedural computed tomography, and horizontal aorta was defined as an aortic angle > 60°. Patients were categorized into horizontal aorta and non-horizontal aorta groups. The incidence, number, and volume of new DW-MRI lesions were compared between groups. Results: The median age was 74.0 years (interquartile range [IQR]: 69.0 to 79.0); 54.5% were male, and the median Society of Thoracic Surgeons score was 3.83% (IQR: 2.29 to 6.39). Horizontal aorta was present in 69 patients (16.8%). Procedural complications were infrequent and comparable between groups. Although the incidence of new cerebral infarctions was similar between groups (89.9% vs. 83.0%; p = 0.157), patients with horizontal aorta had more cerebral infarction lesions (median, 4.0 vs. 3.0; p = 0.031), larger total lesion volume (320.0 vs. 180.0 mm3; p = 0.017), and larger lesion volume per infarction (70.0 vs. 51.7 mm3; p = 0.036). Multivariable analysis identified horizontal aorta as an independent predictor of the number of post-TAVR cerebral infarctions. Conclusions: Horizontal aorta is relatively common among patients undergoing TAVR and is independently associated with a greater burden of DW-MRI-detected subclinical cerebral ischemic injury.